2019 IEEE International Symposium on Circuits and Systems (ISCAS) 2019
DOI: 10.1109/iscas.2019.8702692
|View full text |Cite
|
Sign up to set email alerts
|

A High Bandwidth Modified Regulated Cascode TIA for High Capacitance Photodiodes in VLC

Abstract: This paper proposes, for the first time, a modification of the conventional regulated cascode (RGC) amplifier which improves its tolerance to ultra-high photodiode capacitances. In conventional RGCs, there is a Miller capacitance introduced by the base-collector capacitance of the common base stage, limiting bandwidth gain and potentially result in amplifier instability. Here, we eliminate these undesirable characteristics by introducing an additional cascode stage that nullifies the Miller capacitance. We sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The same group has provided a review article on the design of optical front-end design for high-speed OWCs [23]. Moreover, there has been very interesting research on ultra-low impedance transimpedance amplifiers which lead to significant bandwidth enhancements [24]. This is because the dominating time constant which determines the device bandwidth is a product of capacitance and resistance.…”
Section: (B) Optical Front-end Systemsmentioning
confidence: 99%
“…The same group has provided a review article on the design of optical front-end design for high-speed OWCs [23]. Moreover, there has been very interesting research on ultra-low impedance transimpedance amplifiers which lead to significant bandwidth enhancements [24]. This is because the dominating time constant which determines the device bandwidth is a product of capacitance and resistance.…”
Section: (B) Optical Front-end Systemsmentioning
confidence: 99%
“…In,TIA2,(f)=In,res2,(f)+In,dev2,(f). ${I}_{n,TIA}^{2},(f)={I}_{n,res}^{2},(f)+{I}_{n,dev}^{2},(f).$ The feedback resistor noise is remains uniform with frequency and is given by Equation (), and the noise from the device channel is given by Equation () In,res2=4KTRfb, ${I}_{n,res}^{2}=\frac{4KT}{{R}_{fb}},$ In,dev2,(f)=4KTnormalΓ1gmRfb2+4KTf2normalΓ(2π×CT)2gm. ${I}_{n,dev}^{2},(f)=4KT{\rm{\Gamma }}\frac{1}{{g}_{m}{R}_{fb}^{2}}+4KT{f}^{2}{\rm{\Gamma }}\frac{{(2\pi \times {C}_{T})}^{2}}{{g}_{m}}.$ Figure 3 shows the simulation of input‐referred noise with respect to frequency for different values of Rfb ${R}_{fb}$. A high value of Rfb ${R}_{fb}$ results in low noise and high sensitivity 13 . However, from Equation () it is observed that bandwidth decreases with an increase in Rfb ${R}_{fb}$.…”
Section: Discussionmentioning
confidence: 99%
“…Using inductive peaking techniques, high speed is achieved at the cost and power 4 . Various inductorless TIA topologies proposed are available in the literature 2–16 . Some of them to mention are regulated cascode circuit based TIAs 2,6–9 and inverter based TIA 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A limitation on the bandwidth is mainly introduced by the light-emitting diodes (LEDs) that are commonly used as the transmitter, which reduces the raw modulation bandwidth to a few MHz [1], [2]. At present, Gb/s transmission speeds have been achieved that utilise four key methods including (i) bandwidth expansion by circuit designs, which uses circuit elements to equalise the capacitive behaviour of the LEDs [3] and photodetectors [4]; (ii) advanced modulations, which are used to maximise the number of bits/symbol that can be transmitted on a single This work is supported by the UK EPSRC grant EP/P006280/1: MARVEL, CTU Prague and KU Leuven (CELSA) project "Polarization In wireless CommuNICations (PICNIC)" and by the European Union's Horizon 2020 research and innovation programme under the Marie Sklodowska-Curie grant agreement no 764461 (VISION). wavelength [5]; (iii) digital signal processing (DSP), i.e.…”
Section: Introductionmentioning
confidence: 99%